Teachers' beliefs about multilingual pedagogies and the role of initial training - Portolés, Laura; Martí, Otilia (International journal of multilingualism, 2020)
Teacher training programmes have often ignored the new multilingual paradigm and, consequently, educators may hold some misconceptions about how additional languages are learnt and should be taught in multilingual contexts. A number of recent studies have investigated language teachers' beliefs regarding multilingual education [Arocena-Egaña, E., Cenoz, J., & Gorter, D. (2015). Teachers' beliefs in multilingual education in the Basque country and in Friesland. Journal of Immersion and Content-Based Language Education, 3(2), 169-193; De Angelis, G. (2011). Teachers' beliefs about the role of prior language knowledge in learning and how these influence teaching practices. International Journal of Multilingualism, 8(3), 216-234; Griva, E., & Chostelidou, D. (2012). Multilingual competence development in the Greek educational system: FL teachers' beliefs and attitudes. International Journal of Multilingualism, 9(3), 257-271; Haukås, Å. (2016). Teacher's beliefs about multilingualism and a multilingual pedagogical approach. International Journal of Multilingualism, 13(1), 1-18; Mitits, L. (2018). Multilingual students in Greek school: teachers' views and teaching practices. Journal of education and e-learning research, 5(1), 28-36. Otwinowska, A. (2014). Does multilingualism influence plurilingual awareness of Polish teachers of English? International Journal of Multilingualism, 11(1), 97-119]. Unlike this extant literature, the current paper focuses not on language teachers, but on a sample of 121 subject teachers-to-be. More specifically, it aims to explore preschool and primary prospective teachers' beliefs about the learning and teaching of English as an L3 in the Valencian Community. The main data collection tool was a questionnaire, partially based on [Griva, E., & Chostelidou, D. (2012). Multilingual competence development in the Greek educational system: FL teachers' beliefs and attitudes. International Journal of Multilingualism, 9(3), 257-271] semi-structured interviews. This questionnaire was implemented as a pretest and as a posttest in order to analyse the effect of instruction for multilingual education on subject teachers' beliefs. Results point to the effectiveness of initial teacher training on tertiary/additional language teaching. However, they also confirm the persistence of some monolingual views concerning key issues, such as the younger-the better myth, as already highlighted in previous studies conducted in similar multilingual contexts (see Arocena-Egaña, E., Cenoz, J., & Gorter, D. (2015). Teachers' beliefs in multilingual education in the Basque country and in Friesland. Journal of Immersion and Content-Based Language Education, 3(2), 169-193].